Os torcedores do futuro: as motiva????es que levam jovens paulistanos a se envolver com clubes de futebol da europa - Chaves, Rafael Alberico (2016)
European football clubs are increasingly present in the daily lives of Brazilian fans. Researches point to an accelerated growth of youth involvement level with these clubs. This survey was conducted to find out the main reasons why young people from S??o Paulo to engage with football clubs in Europe, and so it was used the theoretical model TSI (Team Sport Involvement) to reach the main goal of the study. It is characterized as exploratory, qualitative and as a data collection instrument, twelve youth participated in two focus groups discussing seven themes that led us to certain conclusions based on theories. The results point to variables such as interest on the players, the club, the entertainment value, socialization, the possibilities for interaction through digital media, fantasy leagues and video games as the main reasons for young people to get involved with these teams. The study contributes to the understanding of sports managers as to marketing stimuli that can approach the Brazilian teams that consumer profile. The survey also alert to the increased involvement of Brazilians with these clubs, and in extreme cases, identifying theirselves, which already means a paradigm shift in this context.